BASIC STUDY ON THE RECTANGULAR NUMERIC KEYS FOR TOUCH SCREEN - KATSUURA, Tetsuo; HARADA, Hajime; KIKUCHI, Yasuyuki (Journal of Human Ergology, 1997)
The present study was conducted to examine the optimum inter-key spacing of numeric rectangular keys for touch screens. Six male students (22-25 years old) and three female students (21-24 years old) participated in the experiment. Each subject performed the data entry task using rectangular keys of touch devices. These keys were arranged in both horizontal and vertical layouts. The sizes of the rectangular keys in both layouts were 12 x 21 mm and 15 x 39 mm, and each of the inter-key spacing of each key was 0, 3, 6, 12 and 21 mm. The response time with inter-key spacing of 3 mm was significantly faster than with the inter-key spacing of 0, 12 and 21 mm (p < 0.05). Keys of vertical position produced faster response time than that of horizontal position. The subjective ratings showed that the inter-key spacing of 6 mm was significantly better than the inter-key spacing of 0, 3, 12 and 21 mm (p < 0.05).